State power and governance in early Imperial China: the collapse of the Qin Empire, 221-207 BCE - Tong, Chun Fung (SUNY Press, 2024)
"Offers a new perspective on the Qin dynasty in early China and the reasons for its collapse"--
Keywords: China -- Politics and government -- 221 B.C.-220 A.D; Alte Welt; Ancient World; China; Hochschulschrift; Geschichte 221-207 v. Chr.; Krise; Verwaltung; Staat; Qindynastie